Modelling erosion risk at Mountain Penteli (Athens-Greece). - Centeri, C.; Evelpidou, N.; Vassilopoulos, A.; Vaiopoulos, D.; Daniilidis, A. (3rd Magyar Földrajzi Konferencia, 2006)
Development of accurate and efficient models on erosion risk mapping are difficult to be applied on different environmental parameters, mainly due to the complexity of the integrated parameters. In this study the developed GIS model is based on the theory of Boolean logic. The rules integrate the main parameters for erosion, e.g. vulnerability, slope, drainage density, although it is easy for more parameters to be added. As case study area Penteli mountain (North-East Attiki) was selected, that suffers from intense erosion, mainly due to the last severe fire events. With the aim of restraining erosional processes, combinatory strategies, such as assignment of tree trunks parallel to contours, have been applied. The results of this study include a model for erosion, deposition and material transfer. Complementary, a GIS based model was developed so as to define the movement of eroded material within the different drainage basins of the area. The model defines the erosional and depositional sites and the results are confirmed by the measurements on the tree trunks.